The Ethical Dimension of Cognition of Literary Artworks. Post Scriptum to Ingarden’s Theory of Literary Works - Domeracki, Piotr (Roczniki Filozoficzne, 2025)
In this article I critically review Roman Ingarden’s theory of the literary work. In it, he distinguishes three fundamental attitudes in the cognition of a literary work: research, practical everyday life and contemplative-aesthetic. The position taken by Ingarden on this issue seems to me incomplete. Comparing it with the approach represented by Tadeusz Czeżowski on the attitudes taken by the cognitive subject towards the world, which includes attitudes towards human creations such as literary works, I notice a significant difference. This is because Czeżowski, apart from cognitive and aesthetic attitudes, excluding practical-life ones, also takes into account a valuing attitude, one that develops a moral sense. Referring to Ingarden’s works which are representative for the problem discussed, and referring to the second literature which is authoritative for the examined issue, I conclude that Ingarden seems to confine himself in his theory to the logical and aesthetic layer of a literary work, losing sight of the ethical one.